History of the Montreal Young Men's Christian Association - Sandham, Alfred (s.é., 1873)
Keywords: Massey, Samuel; YMCA

Histoire de la charité à Montréal - Germano, J. (Revue canadienne, 1896)
Tome: 9
Keywords: Communautés religieuses

Le bureau des pauvres de Montréal - Bellemarre, Raphaël (Bulletin des recherches historiques, 1899)
Keywords: Bureau des pauvres

Life of the Venerable M.-M. Dufrost de Lajemmerais, Mde d'Youville - Ramsay, D.S. (Grey Nunnery, 1896)
Keywords: Communautés religieuses; Dufrost de Lajemmerais, Marie-Marguerite (Youville, Marguerite d'); Soeurs Grises